Developing a Sharia Mobile Banking Strategy to Enhance Financial Literacy and Digital Inclusion for Underbanked Financing Customers - Sanny Marselina; Manahan Parlindungan Saragih Siallagan (SEIKO : Journal of Management & Business, 2025)
This paper develops a pragmatic strategy for launching a Sharia-compliant mobile banking application at Bank Tepat Syariah to enhance financial literacy and improve access to finance for underbanked financing customers. Although smartphone penetration in Indonesia is high, adoption of mobile banking among financing customers remains low. Based on twenty-four semi-structured interviews with internal stakeholders, field officers, and current and potential customers, complemented by secondary data and regulatory documents (POJK 13/2021; POJK 21/2023), the study identifies three interlinked barriers: (1) Financial Literacy & Digital Confidence Gaps, (2) Behavioral Resistance & Social Influence, and (3) Perceived App Complexity & Usability Barriers. These findings inform an Integrated Adoption Strategy Framework consisting of three pillars—Embedded Financial Literacy, Behavioural Reinforcement, and Simplicity-by-Design—implemented through a phased pilot–scale–launch roadmap aligned with Sharia governance and the three-lines-of-defense risk framework. The paper offers a human-centred, Sharia-compliant blueprint for digital transformation in an underbanked context, positioning mobile banking not only as a transaction channel but also as a vehicle for financial capability and inclusion.